Evaluation of Antimicrobial, Antifungal and Phytochemical Properties of Bauhinia variegata - Mishra, Nidhi Patearia; Verma, Archana (Current Research in Pharmaceutical Sciences, 2014)
Medicinal plants have played an essential role in the development of human culture. Plant products have been part of phytomedicines since time immemorial. The phytochemical research based on ethno pharmacological information is generally considered an effective approach in the discovery of new anti-infective agents from higher plants. These can be derived from any part of the plant like bark, leaves, flowers, seeds, etc i.e., any part of the plant may contain active components. In the present work, qualitative phytochemical analysis was carried out of Bauhinia variegata of Caesalpiniaceae in three different solvents viz. ethanol, methanol and water. During the antimicrobial study it was observed that the ethanolic and methanolic extracts of leaves and stem of Bauhinia variegata showed best results against S.aureus (19mm) and P.aeruginosa (19mm) respectively among the bacterial strains and in fungal strains it gave good results in C.albicans (17.25mm) and C.albicans (16mm). The preliminary phytochemical screening of leaves and stem of Bauhinia variegata showed the presence of alkaloids, carbohydrates, glycosides, flavonoids, phenols, tannins, lignin, saponins, terpenoids and amino acids in all the three solvents used. The present investigation reported the crucial fact that phytochemicals present in different extracts of selected plant parts are highly responsible for their ethnomedicinal and antimicrobial potency.